Study on operational characteristics of low power atmospheric pressure microwave plasma spray method - Ahmad Redza, Ahmad Mokhtar (2016)
Plasma spraying method is the most versatile coating technique for the deposition of high melting point materials such as ceramics and cermet which is used in the application of wear, corrosion and heat resistance. It uses the heat source generated by direct current, radio frequency or microwave as the power source to melt the spray particles which were injected either axially or radially inside the plasma plume. The accelerated particles will collide and impinged onto the surface of the substrate to fabricate the coating. Conventional plasma spray method possesses very high temperature plasma (above 10000 K) athigh power (above 40 kW) which is very useful to fabricate high melting point material coating. However, the excessive heat input from the plasma may influence in deterioration of material phase structure in some material such as ceramics and degraded some functions as well as the difficulty to fabricate coating onto low melting point substrate such as plastics, resin and polymers. Here, the need of using low power plasma to reduce the heat input onto spray and substrate material is being focused and microwave plasma is seen as a good candidate due to its stability in wide range of pressure and easy to be generated at low power. Microwave is rarely been used as the plasma power source due to the unknown mechanism and the stabilization factor of the process. Our research group has managed to generate the plasma with microwave at 1.0 kW of power in atmospheric condition and succeeded to fabricate Cu, Al and Hydroxyapatite coating. However, the mechanism and characteristics of the process is not studied well yet. Thus, the main objective of this research is to study the operational characteristics of low power microwave plasma spray method and its applicability in reducing heat input towards spray and substrate materials as the specialty of this technique. Moreover, the improvements and renovation of the spray device are also studied and presented.